FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DI TRANSMART TEGAL DAN HARGA SEBAGAI VARIABEL MODERATING - Ardina Wuri Hermayanti; Imam Tazali (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2020)
This study aims to determine the factors that influence consumers with price as a moderating variable on purchasing decisions for visitors to Transmart Tegal. The independent variables studied were; service quality variable (X1), Product Completeness (X2), Location (X3) and price (Z), and the dependent variable is the decision (Y) on Tegal Transmart visitors. This type of research uses quantitative research with an associative research approach. The population in this study is to take a sample from the population randomly to a certain number of visitors to Transmart Tegal. The sample used is a non-probability sampling technique, namely the incidental sampling technique with a total of 50 respondents. Data were collected using a questionnaire and analysis techniques using the multiple regretion program (multiple regression). The results of this study prove that: Partially, service quality has a positive effect on purchasing decisions, product completeness has no effect on purchasing decisions, while location has a positive and significant effect on purchasing decisions. Based on the absolute difference test analysis to determine the alleged price variables affecting the relationship between service quality, product completeness and location on purchasing decisions, it is concluded that the price variable does not moderate the relationship between each variable service quality, product completeness and location on purchasing decisions. This research contributes to retail business actors in the modern market to further improve innovation and strategies in increasing consumer purchasing power, especially when unexpected conditions are caused by external factors such as the current pandemic and the increasing competition among retail business actors. developing accompanied by technological advances.